Penguatan Literasi Keuangan Terhadap Orang Tua Dan Siswa SD Di Kampung Kukuk Sumpung Melalui Penguatan Budaya Menabung - Wiryanto, Fadhli Suko; Septyan, Krisno; Praptiningsih, Praptiningsih (Pengmasku, 2023)
Saving is an activity of setting aside some of the money or income you have to be saved for the purpose of managing the money. Seeing a lack of behavioral awareness saving students in Kukuk Sumpung Village, Gobang Village, Rumpin District, Bogor Regency, UPNVJ Lecturers and Students have the desire to provide guidance on how important it is to save and have a frugal lifestyle. for elementary school students and their parents by doing strengthening financial literacy and conducting outreach to students by involving students to help the school carry out fun teaching and learning activities and bring out innovations. Research with using this qualitative method was carried out in one of the villages at the top of Mount Eusing by giving lectures, in-depth observation and observations, socialization and practical teaching. Research result shows that the counseling carried out has helped the implementation of teaching and learning activities. By using Qualitative methods, in this case are used to measure the extent of students' awareness about saving, and students' knowledge in carrying out practices which are the result of socialization This was done to find out whether students can apply a frugal lifestyle in their daily lives.